(3TQM dGejI GdCaYGd dEHf eGdcs - (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s
(3ChdgG (B:s
(3JHOF HGdcdGe Yf GdaYd GdeVGQY Hbhdg(B: (3Ef de jVGYa hde jTgQ HcShI ChVe cjHZi heG UQaJ ef ONdG s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B223 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B130s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B18 - (3U (B401 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdUQas